PENGARUH TERAPI RELAKSASI NAPAS DALAM (DEEP BREATHING) TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS KOTA WILAYAH SELATAN KOTA KEDIRI - Kurnia, Erlin; Suwardianto, Heru (Jurnal Penelitian STIKES Kediri, 2011)
ABSTRACT Hypertension is a result of blood circulation problem. If a patient does not get proper treatment her/his condition will be worse. Therefore the number of morbidity and mortality will progressively increase and health problem in society will be hard improved. The objective of this research was to analyze the influence deep breathing relaxation therapy toward the change of blood pressure on hypertension’s patient at Puskesmas Kota Wilayah Selatan Kota Kediri. The design of this research was quasy experiment non equivalent control group design. Population was the hypertension’s patient at Puskesmas Kota Wilayah Selatan Kota Kediri. The samples were 44 respondents based on inclusion and exclusion criterion on purposive sampling. The independent variable was deep breathing relaxation therapy and the dependent variable was blood pressure. The data was collected using mercurial sphygmomanometer. It was analyzed using paired sample t test and independent samples t test with significant level α < 0.05. The result showed that systolic blood pressure and diastolic blood pressure of control group did not significantly change (p systolic=0,665 and p diastolic=0.825), while the blood pressure of experiment group significantly decrease (p systolic=0.000) and p diastolic=0.000). It was proved by the difference between experiment group and control group (p systolic=0.000) and p diastolic=0.000). Practicing deep breathing relaxation therapy for 15 minutes can decrease systolic blood pressure and diastolic blood pressure. The different mean of systolic blood pressure and diastolic blood pressure decrease were 9.00 mmHg and 10.00 mmHg. The different mean of systolic blood pressure decrease on experiment group was 50 times than the result in control group, while the different mean of diastolic blood pressure experiment group was 111.11 times than the result in control group. The conclusion there was significant influence of deep breathing relaxation therapy toward the change of blood pressure. Keywords: blood pressure, hypertension, deep breathing relaxation therapy